Medical error - Piryani, R M (Journal of Chitwan Medical College, 2015)
Most staffs agreed, for good reasons of honesty and patient autonomy, that admission of errors is important, but the doctors struggled to decide how it should be done. Most agreed that the socio-legal climate in Nepal, and the possible financial implications, made it difficult to be completely honest. Other strong fears included violence from the patient, damage to the hospital’s reputation and to the reputation of the doctors and possible loss of jobs for nurses. The situation seems to be more or less same in other hospitals of Nepal. It is imperative for every hospital in Nepal to have a clinical ethical committee to look after this matter. There must be appropriate hospital policy on dealing with errors. Hospital staffs need specific training in reporting and disclosing error. DOI: http://dx.doi.org/10.3126/jcmc.v4i4.11954